The consequences of early menopause and menopause symptoms for labour market participation. (January 2022) - Bryson, Alex; Conti, Gabriella; Hardy, Rebecca; Peycheva, Darina; Sullivan, Alice
Abstract: Using a difference-in-difference estimator we identify the causal impact of early menopause and menopause symptoms on the time women spend in employment through to their mid-50s. We find the onset of early natural menopause (before age 45) reduces months spent in employment by 9 percentage points once women enter their 50s compared with women who do not experience early menopause. Early menopause is not associated with a difference in full-time employment rates. The number of menopause symptoms women face at age 50 is associated with lower employment rates: each additional symptom lowers employment rates and full-time employment rates by around half a percentage point. But not all symptoms have the same effects. Vasomotor symptoms tend not to be associated with lower employment rates, whereas the employment of women who suffer psychological problems due to menopause is adversely affected. Every additional psychological problem associated with menopause reduces employment and full-time employment rates by 1–2 percentage points, rising to 2–4 percentage points when those symptoms are reported as particularly bothersome. Highlights: Early natural menopause substantially reduces employment rates among women. The number of menopause symptoms women face is also associated with lower employment rates. These effects are larger for symptoms which women say "bother me a lot". Psychological problems due to menopause are associated with the biggest employment effects.